Evaluation of thiol disulfide balance in adolescents with vitamin B12 deficiency - Mehmet Semih Demirtas; Huseyin Erdal (BMC, 2023)
Abstract Background Vitamin B12 is an important vitamin for metabolism and affects many mechanisms in the body including neuronal migration, DNA synthesis, neurotransmitter synthesis, brain and cognitive development. Increased oxidative stress in the body leads to the damage of the child development, but also plays a crucial role in the pathogenesis of many diseases encountered in the childhood period. Our aim is to investigate whether or not B12 deficiency is associated with dynamic thiol/disulfide homeostasis in adolescent patients. Methods This is a case-controlled observational study consisting of 45 adolescent patients with vitamin b12 deficiency and a control group consisting of 45 healthy adolescent. Patients between 11 and 18 ages who applied to the outpatient clinic for the first time with one of the complaints of headache were selected due to their decreased school performance, dizziness, and fatigue. Hemogram, vitamin B12, homocysteine levels and oxidative stress parameters such as native and total thiol disulfide levels and ratios of disulfide/native thiol, disulfide/total thiol, and native thiol/total thiol were measured from the patients. Results Vitamin B12 level was found to be significantly lower in vitamin B12 deficiency group (p < 0.001). The serum disulfide level was found to be 27.5 ± 8.38 in the case group and 20.5 ± 8.36 in the control group (p < 0.001). In the multiple linear regression analysis, it was determined that the independent variables of native thiol, homocysteine and disulfide levels effected of vitamin B12 levels (p < 0.001, p < 0.001, p < 0.005 respectively; R2 = 0.62). Conclusion The results obtained in terms of the effect of vitamin B12 deficiency on oxidative stress in adolescents are remarkable. The increase in oxidative stress parameters in the patient group may also suggest that oxidative stress plays a vital role in vitamin B12 deficiency in adolescence.